A COMPARATIVE INVESTIGATION OF EFFICACY AND COMPLICATIONS IN LIGHT AND DEEP CHEMICAL PEELS (The Research of Medical Science Review, 2025)
Chemical peels are used in dermatological practices to enhance skin texture, tone, and color. They are classified as Light, Intermediate, and Deep BURNS depending on the ward they cause, their consequences on the skin, and different complication rates. This paper looks at the essential factors concerning chemical peels and the difference in the response the treatment receives from men and women. The objective is to evaluate the efficacy and side effects ratio of deep and light chemical peeling and investigate gender differences in results. This was a comparative cross-sectional study of 68 patients undergoing light or deep chemical peeling. The patients were earmarked into two groups depending on the type of peel done equally. The effectiveness of the treatments was determined concerning the extent to which marks on texture and skin tone altered while complications were noted. Self-administered questionnaires were also completed to assess the patient’s satisfaction and perceived improvement in skin quality. Efficacy and complications were also compared between genders to see if there was a gender preference in the results. It was observed that deep chemical peels found a positive change in skin texture and skin tone compared with light chemical peels. Nonetheless, the patients who underwent deep peeling reported more side effects. The analyses of female and male skin after treatments showed that all the surveyed females reported a higher perceived improvement of skin quality and a higher efficacy of both light and deep peels than males; however, females had a statistically significantly higher rate of complications than males. There was evidence of greater effectiveness of the deep chemical peels compared to the light chemical peels, although a higher risk of side effects accompanied this. Sex-specific responses to treatment imply that dermatological treatment should be individualized according to skin pathology and the sex of the patient.